THE EFFECT OF INFLATION, INTEREST RATES, AND GROSS DOMESTIC PRODUCT ON THE RUPIAH EXCHANGE RATE IN INDONESIA IN THE PERSPECTIVE OF ISLAMIC ECONOMICS FOR THE PERIOD 2015-2024 - Ahmad Zaki Alhafidz; Rahmat Fajar Ramdani; Diah Mukminatul Hasimi (Politeknik Negeri Ambon, 2026)
Introduction: The stability of the rupiah exchange rate is essential to the Indonesian economy, especially amid intense global dynamics between 2015 and 2024. This period is marked by fluctuations in commodity prices and geopolitical uncertainty. This study aims to analyse the influence of Inflation, Interest Rates, and Gross Domestic Product (GDP) on the Rupiah Exchange Rate and to interpret these findings from the perspective of Islamic economics, which emphasises real stability and justice. The research method uses a quantitative approach, using secondary quarterly data.Methods: The analysis was conducted in EViews 12, employing panel data regression with the Fixed Effects Model (FEM) following panel model selection testing. The dependent variable is the rupiah exchange rate, while the independent variable includes inflation, interest rates, and GDP. Result: Data is obtained from official publications of Bank Indonesia and the Central Statistics Agency. The results of the study show that inflation has a positive but insignificant effect on the rupiah exchange rate. Meanwhile, interest rates have a positive and significant effect, meaning that interest rate hikes encourage rupiah appreciation through inflows of foreign capital. GDP also has a positive and significant effect, indicating that real economic growth strengthens the rupiah exchange rate. From an Islamic economic perspective, these findings are in line with the concept that the strength of currency value is sustained by real economic activity, stable monetary policy, and the avoidance of speculative practices. The stability of the rupiah exchange rate during the study period was primarily influenced by fundamental variables such as interest rates and GDP, whereas inflation had no significant effect. This shows that stable real and monetary sector-based economic policies align with Islamic economic principles in maintaining the currency's value. Keywords: GDP, Inflation, Interest Rate, Islamic Economy, Rupiah Exchange Rate